Analisis Tingkat Kualitas Pelayanan Pengguna KRL (Kereta Rel Listrik) - Wahid Husein Almunawwar (Universitas Slamet Riyadi, 2024)
Jabodetabek Commuter Line KRL is a public transportation that is now widely used by thegeneral public. The purpose of this study was to analyze the service quality and customer satisfaction of Jabodetabek KRl in the eyes of its users. This study uses the literacy study method in whichresearch uses journals available in electronic media. The results of this study show that the service quality of the Jabodetabek KRl has been satisfactory for its users. However, there are still someaspects that need to be improved. Overall, the users are satisfied and the Jabodetabek KRL has a goodreputation or image in the eyes of its users.